TINGKAT URGENSI PENGUJIAN POLUSI GAS BUANG KENDARAAN BERMOTOR DI INDONESIA - Toto Hardianto; Aryadi Suwono; Suyitno Suyitno (Mesin, 1997)
Until now, Indonesia does not have any dynamics exhaust pollution test standard, which is customized to Indonesian trafï¬c and climate. On the other hand, the air pollution problem in Indonesian big cities has reached a critical level.Some researches done by some institutions (including ITB) show that the air pollution level in Jakarta and some other big cities is mainly caused by transportation, industry, domestic, and trash burning. Among those four pollution sources, transportation (motorized vehicles) is the most signiï¬cant. Therefore, in order to solve the air pollution problem effectively, it has to be started from the transportation sector, and It is very important to do an intensive research which leads to a establishment of a test standard for exhaust gas pollution that is designed based on Indonesian condition.The application of a suitable dynamics exhaust gas pollution test standard is expected to support the pollution monitoring and control activities all over Indonesia, especially in big cities, so that the Indonesian air pollution can be reduced and maintained in a save level.